Curcumin derived from medicinal homologous foods: its main signals in immunoregulation of oxidative stress, inflammation, and apoptosis - Hu, Ping; Li, Kaiqi; Peng, Xiao-Xu; Kan, Yufei; Yao, Tong-Jia; Wang, Zi-Yu; Li, Zhaojian; Liu, Hao-Yu; Cai, Demin (Frontiers in Immunology, 2023)
It has been for thousands of years in China known medicinal homologous foods that can be employed both as foods and medicines to benefit human and animal health. These edible herbal materials perform divert roles in the regulation of metabolic disorders, cancers, and immune-related diseases. Curcumin, the primary component derived from medicinal homologous foods like curcuma longa rhizome, is reported to play vital actions in organic activities, such as the numerous pharmacological functions including anti-oxidative stress, anti-inflammation and anti/pro-apoptosis in treating various diseases. However, the potential mechanisms of curcumin-derived modulation still need to be developed and attract more attention worldwide. Given that these signal pathways are enrolled in important bioactive reactions, we collected curcumin's last achievements predominantly on the immune-regulation signals with the underlying targetable strategies in the last 10 years. This mini-review will be helpful to accelerate curcumin and other extracts from medicinal homologous foods use in future human clinical applications.